PEMANFAATAN SOFTWARE MAXIMA VERSI 16.4.2 TERHADAP MATERI INVERS MATRIKS UNTUK MENINGKATKAN UNDERSTANDING OF CONCEPTS AND THE CORRECT COMPLETION RESULT - Risma Rodiah; Ucu Koswara (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Learning about matrix by the computer devices with version 16.04.2 maxima software can help students to solve problems and abstract matrix concepts. To find an inverse matrix, we must first find the determinant and the adjoint of the matrix. In this case, to find the determinants of matrices of order 2×2 and 3×3, we can use the formulas that have been determined. However, this method cannot be used and applied to solve larger cases such as matrices of the order above. An example of a problem in a matrix that cannot use the available formula is to find the determinant of a matrix of order 4×4,5×5, etc. With the Maxima software, this problem will be solved easily and for the manual, students and teachers can use the Gauss-Jordan Elimination Method or OBE and so on. The results of the work provided by the Maxima Program will be the same as the results of manual work, therefore the Maxima Program has proven its validity, so the Maxima Program can help students understand the concept of the inverse matrix material they are looking for